The European Union's Legal Challenge to Indonesia's Nickel Export Ban at the World Trade Organization - Fitriani, Annisa; Putri, Degita Armelia; Kurnia, Kireina Ajeng; Hosna, Asmak Ul (LifeSciFi, 2025)
Abstract The European Union (EU) has filed a lawsuit at the World Trade Organization (WTO) over Indonesia's down streaming policy in the mining industry. Indonesia's policy aims to add value to natural resources through domestic processing. However, the EU argues that it violates WTO rules on non-discrimination and export restrictions. This lawsuit could threaten the development of Indonesia's mining industry by limiting the government's ability to manage its natural resources and implement policies that promote domestic processing. In light of these issues, the purpose of this study is to analyze the impact of the lawsuit on the Indonesian economy, particularly in terms of investment, employment, and environmental sustainability. The use of the internet as a data collection tool allows researchers to access a broad and in-depth range of information according to research needs. The data analysis method used aims to present research results in an organized and easily understandable form. Additionally, it is necessary to explore strategies that Indonesia can adopt to maintain its down streaming policy while fulfilling international commitments. In conclusion, the EU's lawsuit at the WTO highlights the challenges Indonesia faces in implementing its down streaming policy, while calling for a more balanced approach in managing complex international trade relations. Further research is needed to find solutions that can benefit both parties without compromising sustainable development goals.